Morganella morganii septicemia and concurrent renal crassicaudiasis in a Cuvier’s beaked whale (Ziphius cavirostris) stranded in Italy - Romani-Cremaschi, Umberto; Zoppi, Simona; Mattioda, Virginia; Audino, Tania; Marsili, Letizia; Varello, Katia; Iulini, Barbara; Marra, Cristina; Zoccola, Roberto; Battistini, Roberta; Dondo, Alessandro; Garibaldi, Fulvio; et al. (Frontiers in Marine Science, 2023)
Information regarding bacterial diseases in Cuvier’s beaked whale (CBW, Ziphius cavirostris) is scattered and mostly incomplete. This report describes a case of septicemia by Morganella morganii in a juvenile male CBW with concurrent renal crassicaudiasis. The animal stranded along the Ligurian coastline (Italy) and underwent a systematic post-mortem examination to determine the cause of death. Histopathology showed lesions consistent with a septicemic infection, severe meningoencephalitis, and renal crassicaudiasis. An M. morganii alpha-hemolytic strain was isolated in pure culture from liver, lung, prescapular lymph node, spleen, hepatic and renal abscesses, and central nervous system (CNS). The antimicrobial susceptibility profile of the strain was evaluated with the minimum inhibitory concentrations (MICs) method and reduced susceptibility to Trimethoprim-Sulfamethoxazole is reported. Crassicauda sp. nematodes were retrieved from both kidneys. No other pathogens were detected by immunohistochemistry, serology, or biomolecular analyses. Toxicological investigations detected high concentrations of immunosuppressant pollutants in the blubber. The chronic parasitic infestation and the toxic effects of xenobiotics likely compromised the animal's health, predisposing it to an opportunistic bacterial infection. To our knowledge, this is the first description of M. morganii septicemia with CNS involvement in a wild cetacean.